Purification and Characterization of Thermo Stable DNase of Staphylococcus Aureus Isolated from Different Clinical Source (Medico Legal Update, 2021)
Hundred samples were collected from different clinical source. Sixty isolates were identified asStaphylococcus aureus. The ability of S. aureus to produce DNase was examined phenotypically on DNaseagar medium and also by quantitative assay that revealed only 37(66%) of S. aureus were able to producethe enzyme. DNase was extracted, the crude activity and specific activity was 38 (U/ml) and 253.3(U/mg)respectively. The enzyme purified by precipitating with ammonium sulphate at (65-85 %) saturation thenby using ion exchange chromatography in CM cellulose and gel filtration by using Sephadex G150.Purified DNase activity and specific activity was 42 (U/ml) and 4200(U/mg) respectively. The optimumPH for DNase was found to be 8 while the enzyme was stable at wide range of pH (8, 9 and 10) withremaining activity 100%, 90%, 86% respectively. The optimum temperature for DNase was 37 ºC whilethe stability was also at 37 ºC. Results indicate that DNase activity increased when the enzyme wasincubated with 10 mM of each MnCl2, KCl, NaCl, MgCl2, and CaCl2. The molecular weight of DNasewas done by gel filtration and found to be approximately 19KDa.